Using Research to Support Transformative Impacts on Complex, “Wicked Problems” With Pastoral Peoples in Rangelands - Reid, Robin S.; Fernández-Giménez, María E.; Wilmer, Hailey; Pickering, Tomas; Kassam, Karim-Aly S.; Yasin, Apin; Porensky, Lauren M.; Derner, Justin D.; Nkedianye, David; Jamsranjav, Chantsallkham; Jamiyansharav, Khishigbayar; Ulambayar, Tungalag; et al. (Frontiers in Sustainable Food Systems, 2021)
Pastoralists and researchers (and others) are finding new ways of working together worldwide, attempting to sustain pastoral livelihoods and rangelands in the face of rapid and profound changes driven by globalization, growing consumption, land-use change, and climate change. They are doing this partly because of a greater need to address increasing complex problems, but also with the knowledge that local pastoral voices (and sometimes science) still have little impact on decision-making in the governmental and private sectors. We describe here, using six worldwide cases, how these collaborative partnerships are transforming how we learn about rangelands and pastoralists, whose knowledge gets considered, and even our fundamental model of how science gets done. Over the long-term, collaborative partnerships are transforming social-ecological systems by implementing processes like building collaborative relationships, co-production/co-generation of knowledge, integration of knowledges, social learning, capacity building, networking and implementing action. These processes are changing mental models and paradigms, creating strong and effective leaders, changing power relations, providing more robust understanding of rangeland systems, reducing polarization and supporting the implementation of new practices and policies. Collaborative partnerships have recurring challenges and much work is yet to be done. Challenges include deep inclusion of diverse (and sometimes marginalized) voices, the high complexity of social-ecological problems in rangelands, the time commitment needed to make partnerships work, the bias and naivete of scientists, the recognition that partnerships can promote negative transformations, and the need to attribute impacts to partnership activities. We think that the future of this work will have more focus on systems transformations, morals and ethics, intangible and long-term impacts, critical self-assessment, paradigm shifts and mental models, and power. Overall, we conclude that these partnerships are transformative in unexpected and sometimes intangible ways. Key transformations include changing mental models and building the next generation of transformative leaders. Just as important is serendipity, where participants in partnerships take advantage of new windows of opportunity to change policy or create new governance institutions. We also conclude that collaborative partnerships are changing how we do science, creating new and transformative ways that science and society interact that could be called ‘transformative science with society’.